2022
DOI: 10.1038/s41598-022-14864-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volatile compounds produced by endophytic bacteria on virulence traits of grapevine crown gall pathogen, Agrobacterium tumefaciens

Abstract: The volatile organic compounds (VOCs) produced by endophytic bacteria have a significant role in the control of phytopathogens. In this research, the VOCs produced by endophytic bacteria including Serratia sp. Ba10, Pantoea sp. Sa14, Enterobacter sp. Ou80, Pseudomonas sp. Ou22, Pseudomonas sp. Sn48 and Pseudomonas sp. Ba35, which were previously isolated from healthy domesticated and wild-growing grapevine were evaluated in terms of their effects on the virulence traits of Agrobacterium tumefaciens Gh1, the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Some studies have shown that VOCs released from endophytes can be as biocontrol agents to inhibit the growth of pathogens. 28,29 Strobel et al found that VOCs produced by Muscodor albus had strong antimicrobial activity and could be used to control soil-borne diseases. 30 Zhang et al found that VOCs released by Pseudomonas chlororaphis subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that VOCs released from endophytes can be as biocontrol agents to inhibit the growth of pathogens. 28,29 Strobel et al found that VOCs produced by Muscodor albus had strong antimicrobial activity and could be used to control soil-borne diseases. 30 Zhang et al found that VOCs released by Pseudomonas chlororaphis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that VOCs released from endophytes can be as biocontrol agents to inhibit the growth of pathogens 28,29 . Strobel et al .…”
Section: Discussionmentioning
confidence: 99%
“…Volatile organic compounds are signaling substances that intermediate the interaction between a plant and microbes. Volatile organic compounds are very important, as they help in the inhibition of plant-pathogen growth and induce systematic resistance in a host plant [116] , [121] . Like other bacteria, endophytic bacteria may produce volatile organic compounds such as 2,3-butanediol, acetoin, 2-hexanone, sulfur-containing compounds, 2-heptonone, 3-methybutan-1-ol and dodacanal.…”
Section: Biocontrol Of Plant Pathogensmentioning
confidence: 99%
“…These features that could be useful in biological control have aroused great interest in VOCs released by microorganisms. Many studies on VOCs produced by bacteria have shown that they inhibit the growth of plant pathogens [12][13][14][15][16] . VOCs produced by Pseudomonas uorescens WR-1 can inhibit the growth of Ralstonia solanacearum, the pathogen that causes tomato bacterial wilt, and reduce its pathogenicity [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have reported that Serratia plymuthica, Pseudomonas uorescens and their VOCs have antibacterial activity against A. tumefaciens [18] . In addition, VOCs produced by endophytic bacteria have been suggested to signi cantly reduce the occurrence of grape tumors and cause abnormal morphology of A. tumefaciens cells [14] . These results proved that VOCs produced by biocontrol bacteria play an important role in antagonizing pathogens and interacting with host plants and provided a new source of compounds with antibiotic and plant growth promotion activities.…”
Section: Introductionmentioning
confidence: 99%